Cyclosporine A increases hair follicle growth by suppressing apoptosis‐inducing factor nuclear translocation: a new mechanism. (8th March 2015) - Lan, Shaowei; Liu, Feilin; Zhao, Guifang; Zhou, Tong; Wu, Chunling; Kou, Junna; Fan, Ruirui; Qi, Xiaojuan; Li, Yahui; Jiang, Yixu; Bai, Tingting; Li, Pengdong; et al.
Abstract: Cyclosporine A (CsA) enhances hair growth through caspase‐dependent pathways by retarding anagen‐to‐catagen phase transition in the hair follicle growth cycle. Whether apoptosis‐inducing factor (AIF), a protein that induces caspase‐independent apoptosis, can regulate the hair follicle cycle in response to CsA is currently unclear. Here, we show that the pro‐hair growth properties of CsA are in part due to blockage of AIF nuclear translocation. We first isolate hair follicles from murine dorsal skin. We then used Western blot, immunohistochemistry and immunofluorescence to evaluate the expression and localization of AIF in hair follicles. We also determined whether modulation of AIF was responsible for the effects of CsA at the anagen‐to‐catagen transition. AIF was expressed in hair follicles during the anagen, catagen and telogen phases. There was significant nuclear translocation of AIF as hair follicles transitioned from anagen to late catagen phase; this was inhibited by CsA, likely due to reduced cyclophilin A expression and attenuated AIF release from mitochondria. However, we note that AIF translocation was not completely eliminated, which likely explains why the transition to catagen phase was severely retarded by CsA, rather than being completely inhibited. We speculate that blockade of the AIF signalling pathway is a critical event required for CsA‐dependent promotion of hair growth in mice. The study of AIF‐related signalling pathways may provide insight into hair diseases and suggest potential novel therapeutic strategies.